Analysis of The Resilience Conditions of Individual, Family, and Community during The Covid-19 Pandemic - Hasanah, Viena Rusmiati; Boriboon, Gumpanat; Jubaedah, Yoyoh; Wulandari, Hodijah (Journal of Nonformal Education, 2021)
The COVID-19 pandemic outbreak, a disaster that shocked the whole world, has affected various aspects of people's lives, including the resilience of society, especially the poor. This study aims to see the condition of the resilience of the poor in Bandung in facing the COVID-19 pandemic. The survey method was chosen to obtain the latest data flexibly with a total of 200 respondents, through the distribution of a questionnaire of 40 items consisting of aspects of individual, family, and community resilience. The results show that individual resilience is very dominant during the COVID-19 pandemic disaster, this mutually affects family resilience and community resilience. The most dominant factor in the resilience of individuals and families is the factor of spirituality and optimism in facing this epidemic, the factors that affect community resilience are individual interactions in community activities in the security, social and religious fields